Determining Factors and the Degree of Burden of Nursing Teams in the Care of an Elderly Person with a Neurological Disease - Anna Antczak-Komoterska; Maria Małgorzata Sołtysińska; Natalia Grączewska; Karolina Krajewska; Beata Haor; Dorota Kochman (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. According to the conducted research, the workload results from the general involvement in the undertaken activities. It can therefore be seen that the greater the involvement, the greater the burden, and thus the greater impact on the health of both the physical and mental nurse/caregiver. It should be noted that many factors affect the degree of the load.